A letter concerning toleration concerning civil government, second essay an essay concerning human understanding The principles of human knowledge, An enquiry concerning human understanding - Locke, John frey50; Popple, William (Encyclopedia Britannica Chicago, Illinois, 1952)
A letter concerning toleration, Concerning civil government second essay, Concerning human understanding by John Locke ; Translated by William Popple
The principles of human knowledge by George Berkeley
Concerning human understanding by David Hume
Includes Biographical Note
Keywords: Toleration -- Early works to 1800; Knowledge, Theory of -- Early works to 1800